Pemanfaatan kecerdasan buatan dalam chatbot tanya jawab fikih: Tinjauan etika dan syariah - Suherman, Sunandar (Maliki Interdisciplinary Journal, 2025)
Rapid advances in artificial intelligence (AI) technology have sparked various cross-sector innovations, including in the religious sphere, with the emergence of fiqh question-and-answer chatbots as one of the most prominent manifestations. This study aims to comprehensively examine the potential benefits and inherent risks of implementing AI chatbots in the context of Islamic law. Through an extensive literature review and in-depth sharia analysis grounded in the Quran, Hadith, and the views of reputable scholars, this study explores ethical dimensions and scientific validity. The integration of empirical references from the UIN Maulana Malik Ibrahim Malang environment and case studies of real-world fiqh chatbot applications further enriches the analysis. The research findings indicate that while there is significant potential for AI chatbots to democratize access and disseminate religious literacy in a modern and efficient manner, their success heavily depends on strict oversight in content curation and continuous validation by religious authorities. This is crucial to ensure that the information presented remains aligned with the noble principles of maqāṣid syariah (the objectives of Islamic law), so that technological innovation does not compromise scientific integrity and religious truth.